Software Piracy: An Analysis of Protection Strategies - Reavis Conner, Kathleen; Rumelt, Richard P. (Management Science, 1991)
Software piracy by users is generally believed to harm both software firms (through lower profits) and buying customers (through higher prices). Thus, it is thought that perfect and costless technological protection would benefit both firms and consumers. The model developed here suggests that in some circumstances, even with significant piracy, not protecting can be the best policy, both raising firm profits and lowering selling prices. Key to the analysis is joining the presence of a positive network externality with the fact that piracy increases the total number of program users. The network externality exists because consumers have an incentive to economize on post-purchase learning and customization costs.